2017
DOI: 10.1111/ddi.12661
|View full text |Cite
|
Sign up to set email alerts
|

Climate, host phylogeny and the connectivity of host communities govern regional parasite assembly

Abstract: Aim: Identifying barriers that govern parasite community assembly and parasite invasion risk is critical to understand how shifting host ranges impact disease emergence.We studied regional variation in the phylogenetic compositions of bird species and their blood parasites (Plasmodium and Haemoproteus spp.) to identify barriers that shape parasite community assembly.Location: Australasia and Oceania. Methods:We used a data set of parasite infections from >10,000 host individuals sampled across 29 bioregions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 97 publications
(166 reference statements)
1
109
0
3
Order By: Relevance
“…Blackflies have been shown to harbour high diversities of Leucocytozoon parasites within a single species (Murdock, Adler, Frank, & Perkins, ), supporting the idea that vectors may play important roles in facilitating transmission of Leucocytozoon infections across distantly related bird species. Furthermore, many parasites and pathogens can infect unrelated host species with similar ecological niches, such as habitat use, nesting behaviour and diet (Clark et al, ; Poulin, ). Whereas these host traits are often phylogenetically conserved, they may also be influenced by environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blackflies have been shown to harbour high diversities of Leucocytozoon parasites within a single species (Murdock, Adler, Frank, & Perkins, ), supporting the idea that vectors may play important roles in facilitating transmission of Leucocytozoon infections across distantly related bird species. Furthermore, many parasites and pathogens can infect unrelated host species with similar ecological niches, such as habitat use, nesting behaviour and diet (Clark et al, ; Poulin, ). Whereas these host traits are often phylogenetically conserved, they may also be influenced by environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For each of the 69 sampling sites in our dataset, we extracted altitude as well as several long‐term climate variables that could relate to Leucocytozoon infection prevalence by influencing the distributions and densities of vectors (see Appendix S1). Previous studies have found evidence that temperature and precipitation variables, particularly those that capture variation in summer and winter climates, may be linked to important aspects of haemosporidian community assembly and transmission (Clark et al, ; Fecchio, Wells, et al, ; Oakgrove et al, ; Sehgal et al, ). We included maximum temperature of the warmest month, maximum rainfall of the wettest month, minimum temperature of the coldest month and minimum rainfall of the driest month as predictors in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These haemosporidian parasites are globally distributed and diverse in most bird families (Valkiūnas, ; Clark, Clegg, & Lima, ). The ability of these bird parasites to disperse geographically and to shift among avian hosts has played a significant role in their diversification and distribution (Ellis et al, ; Clark et al, ; Fecchio et al, ). However, few empirical studies have assessed how avian haemosporidian diversity and distributions differ across biogeographical regions and latitudinal gradients (Clark et al, ; Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…This means that both geographical range overlap and ecological interactions between donor and potential recipient host species may be important determinants of host shifts (e.g., Clark et al. ). Finally, de Vienne et al.…”
Section: Discussionmentioning
confidence: 99%